The Influence of Ability and Commitment on Employee Performance Through Discipline in Implementing the Banua Sibohou II Village Device Government System - Opernius Zalukhu; Prayoga, Boby Indra; Rambe, Saima (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This research is motivated by concerns over the low performance of village government officials, especially in Banua Sibohou II Village, Alasa Subdistrict, North Nias Regency, due to gaps in employee ability, organizational commitment, and work discipline. The urgency of this study lies in addressing public service quality by strengthening internal human resource factors. The significance of this research rests on its contribution to understanding how employee capacity and commitment influence performance through the mediating role of work discipline. The research method used is a quantitative approach with a causal design. Data were collected through questionnaires distributed to 35 village government employees. The data were analyzed using path analysis to evaluate direct and indirect relationships among variables. Data validation involved classical assumption testing, multiple linear regression, and statistical significance testing. The findings show that both ability and commitment have a significant and positive effect on employee performance, directly and indirectly through discipline. Work discipline also significantly influences performance. The study highlights that improving employee capability and fostering commitment, supported by a strong culture of discipline, is crucial in enhancing government apparatus performance at the village level. Therefore, it is recommended that local administrations implement regular capacity-building programs, strengthen value-based leadership, and enforce consistent discipline to improve overall governance performance.